A Methodological Review of Stimuli Used for Classroom Speech-in-Noise Tests. - Mealings, Kiri; Miles, Kelly; Buchholz, Joerg M. (Journal of Speech, Language & Hearing Research, 2024)
Purpose: Listening is the gateway to learning in the mainstream classroom; however, classrooms are noisy environments, making listening challenging. Therefore, speech-in-noise tests that realistically incorporate the complexity of the classroom listening environment are needed. The aim of this article was to review the speech stimuli, noise stimuli, presentation mode, and presentation levels of current classroom speech-in-noise tests to determine how representative they are of real-world classroom listening. Method: A comprehensive search of Scopus database following the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews guidelines was conducted to identify classroom speech-in-noise tests used in the research literature. The search term was classroom AND (listening OR (speech AND (perception OR intelligibility OR recognition OR discrimination) AND noise) OR speech-in-noise) AND (test OR task OR measure OR assessment) AND children in the article title, abstract, and key word fields. Results: A total of 97 papers met the criteria to be included in the review. While the speech and noise stimuli were generally presented at realistic speech and noise levels, the speech materials were not representative of real-world classroom listening. Additionally, unrealistic noise and presentation modes were used in several studies. Conclusion: This review will help researchers choose appropriate speech-innoise test stimuli in future research and also help researchers understand what to consider when creating new speech-in-noise tests for classroom listening. Supplemental Material: https://doi.org/10.23641/asha.27659619